Trade and macroeconomics: TMD research themes brochure - International Food Policy Research Institute (International Food Policy Research Institute, 2001)
Food and agricultural systems in developing countries connect with the rest of the economy and with the world through a network of markets. Changes in world markets directly affect national economies and changes in domestic nonfood policies indirectly affect food sectors. The Trade and Macroeconomics Division (TMD) analyzes the impact that national policies and the global economic environment have on agricultural performance, food security, natural resource use, poverty, and income distribution in developing countries. Using research methods that examine links across sectors and regions, TMD helps policymakers understand how trade policy, structural adjustment programs, and other macroeconomic policies affect the poor. TMD's work program is designed around two approaches: (1) Macroeconomic Policies, Growth, and Poverty Reduction (MP12): Single-country case studies that examine how sectoral and macroeconomic policies fit together and whether they are adequate for the task of achieving both growth and equity. (2) Global and Regional Trade (GRP2): global analyses that show how changes in regional and global trading arrangements and the worldwide macroeconomic environment affect developing countries, especially their food security and levels of poverty. The division combines research and capacity building by collaborating with institutions and researchers in developing countries and by holding teaching workshops on methods of policy analysis.